Extracellular Vesicles Shed By Trypanosoma cruzi Potentiate Infection and Elicit Lipid Body Formation and PGE2 Production in Murine Macrophages - Lovo-Martins, Maria Isabel; Malvezi, Aparecida Donizette; Zanluqui, Nágela Ghabdan; Lucchetti, Bruno Fernando Cruz; Tatakihara, Vera Lúcia Hideko; Mörking, Patricia Alves; Oliveira, Admilton Gonçalves de; Goldenberg, Samuel; Wowk, Pryscilla Fanini; Pinge-Filho, Phileno (Frontiers in Immunology, 2018)
During the onset of Trypanosoma cruzi infection, an effective immune response is necessary to control parasite replication and ensure host survival. Macrophages have a central role in innate immunity, acting as an important trypanocidal cell and triggering the adaptive immune response through antigen presentation and cytokine production. However, T. cruzi displays immune evasion mechanisms that allow infection and replication in macrophages, favoring its chronic persistence. One potential mechanism is the release of T. cruzi strain Y extracellular vesicles (EV Y), which participate in intracellular communication by carrying functional molecules that signal host cells and can modulate the immune response. The present work aimed to evaluate immune modulation by EV Y in C57BL/6 mice, a prototype resistant to infection by T. cruzi strain Y, and the effects of direct EV Y stimulation of macrophages in vitro. EV Y inoculation in mice prior to T. cruzi infection resulted in increased parasitemia, elevated cardiac parasitism, decreased plasma nitric oxide (NO), reduced NO production by spleen cells and modulation of cytokine production, with a reduction in TNF-α in plasma and decreased production of TNF-α and IL-6 by spleen cells from infected animals. In vitro assays using bone marrow-derived macrophages showed that stimulation with EV Y prior to infection by T. cruzi increased the parasite internalization rate and release of infective trypomastigotes by these cells. In this same scenario, EV Y induced lipid body formation and PGE2 production by macrophages even in the absence of T. cruzi. In infected macrophages, EV Y decreased production of PGE2 and cytokines TNF-α and IL-6 24 h after infection. These results suggest that EV Y modulates the host response in favor of the parasite and indicate a role for lipid bodies and PGE2 in immune modulation exerted by extracellular vesicles.